2017
DOI: 10.1177/0955749017718705
|View full text |Cite
|
Sign up to set email alerts
|

Viral marketing effect on digital knowledge acquisition

Abstract: This study focuses on the growing role of viral marketing in the dissemination and circulation of knowledge via WhatsApp. This application is a favorable viral marketing environment as it allows rapid dissemination of knowledge through the sharing of texts, images, audio, and video files. Many individuals spontaneously practice viral marketing by resending messages they have received to others, thereby delivering content to a large segment of society. This study aims to ascertain the degree of influence of vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The state-owned Al-Ahram and the private newspaper Al-Masry Al-Youm took up the story directly on the next day, 12 June 2010. For the private newspapers, it was ‘initial confusion over the contradicting details of the incident [that] caused the delay in the media coverage, as well as Khaled Said’s family’s reluctance to share the story with the media’, explained Mohamed Fouad, an Alexandrian journalist (Fouad, 2017).…”
Section: Results: Breakthrough Issue Cycles and Contesting Interpretationsmentioning
confidence: 99%
“…The state-owned Al-Ahram and the private newspaper Al-Masry Al-Youm took up the story directly on the next day, 12 June 2010. For the private newspapers, it was ‘initial confusion over the contradicting details of the incident [that] caused the delay in the media coverage, as well as Khaled Said’s family’s reluctance to share the story with the media’, explained Mohamed Fouad, an Alexandrian journalist (Fouad, 2017).…”
Section: Results: Breakthrough Issue Cycles and Contesting Interpretationsmentioning
confidence: 99%
“…The platform is seen as an ideal technological tool for viral marketing, that is, actions that are spontaneously and quickly passed on by people themselves (FOUAD, 2017). Interviews with participants in the Gezi Park protests in 2013 in the city of Istanbul, Turkey, indicated that the application was used for sociability among members and exchange of information for allowing faster download than Facebook groups, in addition to building environments for private and controlled access, more conducive to the development of bonds of affinity and trust within the group (HACIYAKUPOGLU; ZHANG, 2015).…”
Section: Transformation Of Digital Campaign Strategies and Infrastrucmentioning
confidence: 99%
“…Operations is responsible for collecting users’ information and it handles the data warehouse and analytical functions that analyzes this stored information through the use of data mining technology to make this information useful. The analytical side devises several relations from this information to extract new user-related knowledge that is useful in the development of the service provided to the user or in the provision of additional services related to the user (Fouad, 2013: 53–54). Thus, the CRM software is an intelligent and advanced tool that contributes to improving the performance of the enterprise and upgrading its services (Kamal, 2002).…”
Section: Crm Systemmentioning
confidence: 99%
“…There are several options for libraries to adopt a CRM system, (Fouad, 2013: 53–56). Building a local system. Purchasing ready-made software package. Using cloud computing applications. Open source CRM software applications. …”
Section: Crm Systemmentioning
confidence: 99%